P-Selectin Glycoprotein Ligand 1: A Potential HIV-1 Therapeutic Target - Zaongo, Silvere D.; Liu, Yanqiu; Harypursat, Vijay; Song, Fangzhou; Xia, Huan; Ma, Ping; Chen, Yaokai (Frontiers in Immunology, 2021)
Antiretroviral therapy (ART), which is a life-long therapeutic option, remains the only currently effective clinical method to treat HIV-1 infection. However, ART may be toxic to vital organs including the liver, brain, heart, and kidneys, and may result in systemic complications. In this context, to consider HIV-1 restriction factors from the innate immune system to explore novel HIV therapeutics is likely to be a promising investigative strategy. In light of this, P-selectin glycoprotein ligand 1 (PSGL-1) has recently become the object of close investigative scrutiny as a recognized cell adhesion molecule, and has become a major focus of academic study, as researchers believe that PSGL-1 may represent a novel area of interest in the research inquiry into the field of immune checkpoint inhibition. In this article, we review PSGL-1’s structure and functions during infection and/or inflammation. We also outline a comprehensive review of its role and potential therapeutic utility during HIV-1 infection as published in contemporary academic literature.